Land Use in the Southern Cone in the Colonial Period: Colonial Spanish America between the 19º and 34º South Latitude - Gascon, Margarita Susana (2024)
Under the Habsburg regime (sixteenth and seventeenth centuries), the territories of present-day Argentina, Bolivia, Chile, Paraguay, and Uruguay located approximately between the 19º and 34º south latitude (SL) (Fig. 1) were part of the Viceroyalty of Peru. The administrative reorganization of the Bourbons in the eighteenth century brought Cuyo,Upper Peru(now Bolivia) and present-day Paraguay andUruguay under the jurisdiction of the Viceroyalty of the Río de la Plata, founded in 1776. In the territorial strip between 19º and 34º SL, the populations located around 31º formed the southernmost periphery of Spanish America, since Patagonia remained uninhabited by Europeans, as did most of southern Chile after the Great Araucanian Rebellion at the end of the sixteenth century.There was an unsuccessful attempt to establish populations in the Strait ofMagellan around the end of the sixteenth century, but they succumbed to difficult environmental conditions, lack of food, and disease. From the seventeenth century onwards, the frontier with the Indigenous was militarized on the banks of the Biobío River and the main Spanish settlement was Concepción (36ºLS). The indigenous domain began south of 35º SL on both slopes of the Andes and in the lands designated as Trapalanda or Magallanica. Spanish incursions were driven by accounts of the existence of immensely wealthy populations.The legend of the “City of the Caesars,” for example, referred to a fabulous kingdom in some southern confine, with abundant gold and silver, governed by whites (“caesars”) with docile and helpful natives.